1996
DOI: 10.1091/mbc.7.2.307
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and functional analysis of the YME1 gene product, an ATP and zinc-dependent mitochondrial protease from S. cerevisiae.

Abstract: Inactivation of YME1 in yeast causes several distinct phenotypes: an increased rate of DNA escape from mitochondria, temperature-sensitive growth on nonfermentable carbon sources, extremely slow growth when mitochondrial DNA is completely absent from the cell, and altered morphology of the mitochondrial compartment. The protein encoded by YME1, Ymelp, contains two highly conserved sequence elements, one implicated in the binding and hydrolysis of ATP, and the second characteristic of active site residues found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(111 citation statements)
references
References 42 publications
(36 reference statements)
5
106
0
Order By: Relevance
“…Interestingly, sequence analysis shows that the closest homologue of TOB3 in yeast is YME1, a mitochondrial I-AAA protease (Table II). YME1 plays an essential role in the degradation of unassembled or misassembled subunits of cytochrome c oxidase (16). YME1 gene disruption led to several dysfunctions, including a reduced activity of the respiration chain complexes, slow growth, and lethality when the mutation is expressed in a Ϫ mitochondrial background (17).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, sequence analysis shows that the closest homologue of TOB3 in yeast is YME1, a mitochondrial I-AAA protease (Table II). YME1 plays an essential role in the degradation of unassembled or misassembled subunits of cytochrome c oxidase (16). YME1 gene disruption led to several dysfunctions, including a reduced activity of the respiration chain complexes, slow growth, and lethality when the mutation is expressed in a Ϫ mitochondrial background (17).…”
Section: Resultsmentioning
confidence: 99%
“…Both the ATPase activity and Zn-binding activity are required for the correct functioning of these proteins (Weber et al 1996). Members of this protein group have been shown to degrade transcription factors such as 32 (Tomoyasu et al 1995;Herman et al 1995) and phage cII (Arlt et al 1996) protein and probably participate in a number of other cellular functions as well.…”
Section: The Eubacterial Metalloproteasesmentioning
confidence: 99%
“…However, their physiological functions remain to be established. Identification of the 372 Weber et al (1996), however, reported an orientation towards the matrix side. See Table 2 and text for details on the different proteases corresponding genes will be an important step towards that end.…”
Section: Are All Mitochondrial Atp-dependent Proteases Multimers?mentioning
confidence: 90%
“…The latter appears to be degraded by Yme1p. Mutation of YME1 has been found to attenuate degradation of CoxII in the absence of CoxIV (Nakai et al 1995;Weber et al 1996), and a stabilizing effect of YME1-inactivation on both CoxII and CoxIII has been observed in a strain lacking cytochrome c (Pearce and Sherman 1995a). The presence of ATP-and zinc-binding motifs typical of metalloproteases in Yme1p, Rca1p and Afg3p supports the notion that these three proteins are indeed responsible for the degradation of mitochondrial translation products destined for the inner membrane, which, as described above, is both ATP-and divalent metal ion-dependent.…”
Section: Division Of Labourmentioning
confidence: 99%
See 1 more Smart Citation